The Efficacy of Tradipitant in Patients With Diabetic and Idiopathic Gastroparesis in a Phase 3 Randomized Placebo-Controlled Clinical Trial - Carlin, Jesse L.; Polymeropoulos, Christos; Camilleri, Michael; Lembo, Anthony; Fisher, Michaela; Kupersmith, Caleigh; Madonick, Darby; Moszczynski, Paula; Smieszek, Sandra; Xiao, Changfu; Birznieks, Gunther; Polymeropoulos, Mihael H. (Clinical gastroenterology and hepatology, 2024)
Neurokinin receptor 1 antagonists are effective in reducing nausea and vomiting in chemotherapy-induced emesis. We investigated the safety and efficacy of tradipitant, a neurokinin receptor 1 antagonist, in patients with idiopathic and diabetic gastroparesis. A total of 201 adults with gastroparesis were randomly assigned to oral tradipitant 85 mg (n = 102) or placebo (n = 99) twice daily for 12 weeks. Symptoms were assessed by a daily symptom dairy, Gastroparesis Cardinal Symptom Index scores, and other patient-reported questionnaires. Blood levels were monitored for an exposure-response analysis. The primary outcome was change from baseline to week 12 in average nausea severity, measured by daily symptom diary. The intention-to-treat (ITT) population did not meet the prespecified primary endpoint at week 12 (difference in nausea severity change drug vs placebo; P = .741) or prespecified secondary endpoints. Post hoc analyses were performed to control for drug exposure, rescue medications, and baseline severity inflation. Subjects with high blood levels of tradipitant significantly improved average nausea severity beginning at early time points (weeks 2–4). In post hoc sensitivity analyses, tradipitant treatment demonstrated strengthened effects, with statistically significant improvements in nausea at week 12. Although tradipitant did not reach significance in the ITT population, a pharmacokinetic exposure-response analysis demonstrated significant effects with adequate tradipitant exposure. When accounting for confounding factors such as baseline severity inflation and rescue medication, a statistically significant effect was also observed. These findings suggest that tradipitant has potential as a treatment for the symptom of nausea in gastroparesis. (ClincialTrials.gov, Number: NCT04028492). [Display omitted]